The Neurology of Proverbs - Diana Van Lancker (Behavioural Neurology)
Although proverb tests are commonly used in the mental status examination surprisingly little is known about either normal comprehension or the interpretation of proverbial expressions. Current proverbs tests have conceptual and linguistic shortcomings, and few studies have been done to investigate the specific effects of neurological and psychiatric disorders on the interpretation of proverbs. Although frontal lobes have traditionally been impugned in patients who are “concrete”, recent studies targeting deficient comprehension of non literal language (e.g. proverbs, idioms, speech formulas, and indirect requests) point to an important role of the right hemisphere (RH). Research describing responses of psychiatrically and neurologically classified groups to tests of proverb and idiom usage is needed to clarify details of aberrant processing of nonliteral meanings. Meanwhile, the proverb test, drawing on diverse cognitive skills, is a nonspecific but sensitive probe of mental status.